Original paper Single- and multivessel coronary disease associated with ST-segment elevation myocardial infarction. One-year outcomes - Zębik, Tadeusz; Gąsior, Mariusz; Kalarus, Zbigniew; Wąs, Tomasz; Gierlotka, Marek; Lekston, Andrzej; Wilczek, Krzysztof; Hawranek, Michał; Wasilewski, Jarosław; Trzeciak, Przemysław; Tajstra, Mateusz; Zembala, Marian; et al. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2006)
Multivessel coronary disease (MCD) associated with ST segment elevation myocardial infarction (STEMI) deteriorates the clinical outcome. Data on patients with acute myocardial infarction (AMI) and MCD treated with percutaneous coronary interventions (PCI) are limited. Material and methods: A total of 3190 consecutive pts with AMI were included in the analysis. After coronary angiography MCD was diagnosed in 1751 (54.9%) pts. Infarct related artery (IRA) was treated with immediate PCI in both groups. Results: Differences in clinical characteristics were as follows: pts with MCD were older and time from onset to PCI was longer. Hypertension, diabetes mellitus, previous infarction and cardiogenic shock on admission were more frequent in this group and similarly TIMI 0-1 flow was in the initial angiogram. Anterior infarction, preceding thrombolysis and smoking were less frequent. The optimal angiographic effect was achieved more frequently by pts with single vessel coronary disease (SCD). Hospitalization was longer and LVEF was lower in MCD pts group. In-hospital and 1-year mortality was higher (3.5 vs 9.3%, p <0.0001 and 4.2 vs 11.9%, p <0.0001, respectively) in patients with other significant stenoses in the non-infarct related artery. There were no differences in the incidence of reinfarctions and cerebrovascular accidents. Revascularization procedures (PCI and/or coronary artery bypass grafting, CABG) were performed more often during the in-hospital period. In 1-year follow up necessity of PCI in IRA and CABG was less frequent in pts with SCD. At one year a composite of cardiac death, reinfarction, and target lesion revascularization (TLR) occurred more frequently in pts with MCD. In a multivariate analysis MCD (next to age, cardiogenic shock, no reperfusion after PCI, reocclusion, anterior infarction and diabetes) is an independent factor increasing mortality in pts with STEMI treated with PCI in 1-year follow up (odds ratio [OR]=1.92; 95% CI, p<0.0001). Conclusion: Multivessel coronary disease is an independent factor deteriorating prognosis of pts with STEMI. Because the risk of the unfavourable outcome is highest in the first 30 days after STEMI, full revascularization in this subset of patients should be considered at the earliest possible time. Further trials are warranted to explore this problem.